2012
DOI: 10.1002/ejsp.1893
|View full text |Cite
|
Sign up to set email alerts
|

Ambassadors of gender equality? How use of pair forms versus masculines as generics impacts perception of the speaker

Abstract: Although the use of gender fair language is strongly promoted in German‐speaking countries, the impact of its use on the way speakers are perceived by others is still unknown. Results of two experimental studies showed that irrespective of their sex, speakers using pair forms rather than generic masculines were perceived more competent by both men and women. Also, they were seen as less sexist by male and female listeners with positive attitudes towards linguistic equality. Findings with respect to the attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…Consistent with other studies on German (Vervecken and Hannover, 2012), Study 3 on Austrian German showed that designating women with gender-fair (feminine) forms led to higher support for all types of initiative than when the female proponents were labeled with masculine forms. In line with Vervecken and Hannover (2012), we assumed that the use of gender-fair language in German is currently associated with higher education or competence and has lost its novelty as well as its associations with feminism.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Consistent with other studies on German (Vervecken and Hannover, 2012), Study 3 on Austrian German showed that designating women with gender-fair (feminine) forms led to higher support for all types of initiative than when the female proponents were labeled with masculine forms. In line with Vervecken and Hannover (2012), we assumed that the use of gender-fair language in German is currently associated with higher education or competence and has lost its novelty as well as its associations with feminism.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings may offer an explanatory framework for the results of earlier studies, which report both positive and negative speaker perceptions of gender-fair wording (e.g., McConnell and Fazio, 1996; Vervecken and Hannover, 2012). These seemingly contradictory results reflect different stages of adaptation to gender-fair language in the respective societies investigated.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…To test our hypotheses that language form used to describe occupational titles would influence the ascription of warmth and competence to prototypical jobholders, we conducted separate analyses for warmth and competence in line with previous research (e.g., Vervecken and Hannover, 2012; Budziszewska et al, 2014). …”
Section: Resultsmentioning
confidence: 99%